State Policy of Staffing of Global Reindustrialization of National Economy - DANILOV, Ivan P.; ILYINA, Ekaterina A.; LADYKOVA, Tatiana I.; MOROZOVA, Natalia V. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
Relevance of the studied problem is caused by the fact that today the conditions and factors forming the state personnel policy of ensuring global reindustrialization of national economy are insufficiently fully investigated. In this regard this article is directed to development of measures for improvement of the state migration policy, and also the solution of problems of definition of need for foreign labor. The leading approach to a research of this problem is the system approach based on search of the interconnected factors of migration flows and assessment of influence on a resultant sign – the balanced condition of national labor market. The proposed measures of improvement of the state personnel policy include: creation of effective mechanisms of assessment by the regional authorities of the valid need for foreign labor taking into account the long-term prospects of social and economic development of the region, national labor market and improvement of institute of quoting. Materials of article can be useful when developing the effective mechanisms of regulation of external labor migration promoting formation of effective migration policy.